Biased Altruism: Islamophobia and Donor Support for Global Humanitarian Organizations. (27th December 2018) - Tremblay‐Boire, Joannie; Prakash, Aseem
Abstract: Providing humanitarian assistance to displaced individuals is a critical policy challenge. Many refugee camps are run by charities supported by Western donors. If refugees are predominantly Muslim, might Islamophobia suppress donations to these charities? Using a survey experiment conducted in the United States, the authors examine whether donors' willingness to support a charity is influenced by the dominant religion of the refugees, the regions in which refugee camps are located, and/or the religious affiliation of the charity. The authors find modest support for Islamophobia: while willingness to donate is not affected by the location of camps or the predominance of Muslim refugees, it declines significantly for Islamic charities. Respondents overall tend to be especially willing to donate to a charity that serves Christian refugees in the Middle East. Among self‐identifying Christians, respondents are more willing to donate to a charity serving Christian refugees than one serving Muslim refugees .